Assessment of coordination abilities as a criterion for selecting children at the stage of initial training in the Latin American dance sports program - Long, Li; Singina, N.F. (Theory and Practice of Physical Culture, 2026)
This article examines the problem of substantiating the selection criteria at the stage of initial training for those involved in dance sports in the Latin American program. Based on the analysis of scientific and methodological literature, an expert survey of specialists (n=15) and the results of a pedagogical experiment (n=40), it is proved that coordination and balance are the priority criteria for the prospects of dancers. It is concluded that it is necessary to move from the traditional assessment of general physical fitness to a multifunctional profile, where coordination abilities play a system-forming role.